Assessing the quality of service delivery by South African consulting engineers - Stone, John Robert (My University, 2011)
Consulting Engineers provide a service that falls between tangible and intangible. The technical product is strictly controlled by design and quality management standards, rendering it generally homogeneous across consulting organisations. The manner in which the product is delivered, therefore, offers a consulting engineer with a means of achieving differentiation between companies in this mature industry. Assessing the quality of service delivered by South African Consultants is the objective of this research. A number of service quality measurement instruments are available. This research adopted the contemporary SERVQUAL instrument, measuring the Zone-of-Tolerance between minimum acceptable service and desired (or expected) service levels and comparing this to perceptions of service actually delivered. The results of the questionnaire were analysed by correspondence analysis, rescaled to ordinal data and then processed through a factor analysis. The results of the factor analysis were then clustered by K-Means clustering. Normality and reliability were determined by an algorithmic data fitting process, as the survey sample was small. This research demonstrates the disconnect that occur in service industries, where the provider and consumer of the service do not have the same understanding or degrees of expectation regarding the level of service to be delivered. There are clear gaps between client expectations and consulting organisations principals’ perceptions of service requirements. The research also shows that clients do not generally rate service delivery as meeting much more than minimum standards. “Reliability”, “Assurance” and “Communication” are identified as being the three most important underlying dimensions that impact on service quality. These findings emphasise the need for consulting engineering principals to interact more closely with clients, to determine what is important before providing a service. Communication of problems, together with solution proposals and cost estimates, at an early stage is considered critical to clients. Regular project management is also considered essential and is an area of service perceived lacking by clients. Further research in other service industries is needed to confirm these findings. A longitudinal study tracking changes in perception would also greatly increase knowledge in this field
MBA - WBS
Keywords: Engineers, Consulting; Professional services